The Influence of Viable Cells and Cell-Free Extracts of Lactobacillus casei on Volatile Compounds and Polyphenolic Profile of Elderberry Juice - Ricci, Annalisa; Levante, Alessia; Cirlini, Martina; Calani, Luca; Bernini, Valentina; Del Rio, Daniele; Galaverna, Gianni; Neviani, Erasmo; Lazzi, Camilla (Frontiers in Microbiology, 2018)
In this study, four strains of Lactobacillus casei, as viable cells or cell-free extracts (CFE), were added to elderberry juice in order to evaluate their effect on phenolic and aromatic profile. Two of them were able to grow in juice while the others showed zero-growth. The same strains were lysed and added as extracts in elderberry juice. Multivariate statistical analysis show a separation among samples containing growing cells, non-growing cells, CFE, highlighting the particularities of specific strains. Juices added with CFE presented the highest amount of esters. The strains showing growth phenotype cause an increase of phenyllactic acids. The highest concentration of volatile compounds, particularly of alcohols, terpenes and norisoprenoids (responsible for typical elderberry notes) was observed in samples with strains showing zero-growth. Moreover, a significant increase in anthocyanin content was observed in these samples, suggesting the possible use of Lactobacillus for increasing specific molecules, even for non-multiplying bacterial cell. Considering that this is the first study concerning the use of non-growing cells in fruit juice, the potential of strains is still to be explored and it may have a significant technological application in the development of a microbial collection useful for fruit juice industry.